Espaços educadores no contexto do CESCAR (Coletivo Educador de São Carlos, Araraquara, Jaboticabal e Região/SP): do conceito à formação em educação ambiental - Kunieda, Edna (Universidade Federal de São Carlos, 2010)
The Coletivo Educador de São Carlos, Araraquara, Jaboticabal e Região (CESCAR), a environmental educators´s group, is guided by the precepts of Programa Nacional de Formação em EA (ProFEA) a Brazilian environmental education program that adopts the methodology of participatory-action-research proposed by the team of Board of Environmental Education of the Ministry of Environment (MMA). The proposal adopts environmental education (EE) emancipatory, transformative and criticism, fostering networking who values the local and regional initiatives. In order to understand the process of construction of CESCAR, we chose to analyse the phenomenon "educators spaces" by the experience of people who experienced this practice. We use the Hermeneutical methodology in association with Phenomenology, as strands of qualitative research. "Educators spaces" is a recent concept that in the Programa Municípios Educadores Sustentáveis a educational program that involve sustainable cities, offered by the same team of MMA, is defined as one that stimulates collective in improving their training and in the search for viable alternatives to sustainability. We take the research on "educator spaces" as a challenge because it is a concept still under development that requires discussion and build on this theoretical issue. We have established through similarities and oppositions, a framework about some of the spaces experienced by the group of environmental educators, through the analysis of twenty-four monographs. This angle allowed a glimpse of the mosaic of images assigned to the various "worlds lived" as well as to investigate the concept in a symbolic and existential perspective.
Keywords: Educação ambiental; Políticas públicas; Fenomenologia; Ricoeur, Paul teoria da interpretação; Espaços educadores; Coletivos educadores; Fenomenologia-hermenêutica; Educators spaces; Educator collective; Environmental education; Hermeneutic phenomenology; CIENCIAS BIOLOGICAS::ECOLOGIA